Optimasi Fasad Bangunan untuk Efisiensi Energi Berdasarkan Analisis OTTV pada Ruang Dosen Politeknik Negeri Sriwijaya - Nurlatifah Fajriaty Ronyta; Ricky Ravsyan Alhafez; Karina Karina; Ria Dwi Putri; Doni Sastra (Universitas Batanghari Jambi, 2026)
Building facade optimization plays an essential role in improving the energy efficiency of buildings, particularly in tropical regions such as Indonesia, which experience high solar radiation intensity. Educational institution buildings, such as the Lecturer Room of the D-IV Building Architecture Program at Politeknik Negeri Sriwijaya, Keramasan Campus, represent one of the building types with high energy demand for thermal comfort and lighting. The urgency of this research lies in the need for façade design strategies that can reduce cooling loads without compromising thermal and visual comfort, while also complying with energy efficiency standards through the calculation of the Overall Thermal Transfer Value (OTTV). This study aims to examine and optimize the building facade design based on OTTV values in accordance with SNI 03-6389-2011 and the Ministry of Energy and Mineral Resources Regulation (Permen ESDM) No. 02/2021. The research employs a quantitative approach consisting of field surveys, physical data collection of the building, thermal modeling, and simulation of façade optimization through the combination of shading devices and low-e glass. The results show that the existing façade design has an OTTV value of 43.21 W/m², exceeding the maximum limit of 35 W/m². After optimization through the application of horizontal shading devices and the use of low-e glass, the OTTV value decreased to 32.87 W/m², meeting the energy efficiency standard. This research provides recommendations for energy-efficient facade design and serves as a reference for designing educational buildings in hot-humid tropical climates. The findings are expected to contribute to the development of sustainable architectural design practices within campus environments.